How the Mountain Kingdom speaks: forging a national literary tradition in Lesotho - Viriri-Shava, P.; Nyawo-Shava, Vongai Z. (National University of Lesotho: Faculty of Humanities, 2016)
The paper explores the origins and development of Lesotho literature in English. Informed byT.S. Eliot's New Criticism of the dialectic between tradition and the individual talent, the paper places the literature into a national, religions, historical, cultural, political, mythological, geographical, and trans-national context. The article contends that although early writers, such as Thomas Mofolo. Mopeli-Putdus and others pioneered the inception of the literature, there is a tenuous tradition between the writings of the pillars of Lesotho literature in English and those of succeeding literary generations. The paper also argues that, although the literature found its initial expression in the form of the novel, the novel itself, as an art form in Lesotho, has gradually dwindled, giving way to shorter genres such as drama, poetry and the short-story. Periodising the imaginative output from the lime of its nascency to dale, the paper discusses its quantity, quality and future possibilities, thereby foregrounding its social history. identity, autonomy and distinctiveness.